Optimization of Parameters for the Detoxification of Cr(VI) by the Microbial Consortium Developed from the Isolates of Chromite Mines. Issue 3 (2nd May 2022) - Leonard, J.; Mishra, Susmita
Abstract: Hexavalent chromium Cr(VI) is one of the ubiquitous contaminants in Odisha since it is being a rich belt of chromite mines. Discharged water from the mines to the surface water bodies consists of Cr(VI) above permissible limit which can cause numerous health effects. Bioremediation can be an eco-friendly remedy to detoxify the Cr(VI) in which Chromium resistant microorganisms can be used. Three chromium resistant organisms were isolated from the ore soil of chromite mines. Isolated organisms were identified as Serratia nematodiphila, Bacillus cereus and Kocuria rosea using 16S rRNA sequencing. A bacterial consortium was developed with the isolated organisms after their acclimatization. The process parameters such as pH, temperature, inoculum size, inoculum age and carbon source were optimized for maximum Cr(VI) reduction by one variable at a time method. Optimization results revealed that pH of 8.5 and the temperature of 35 °C were the optimum conditions and glucose was an effective carbon source. The Cr(VI) reduction was more effective at the inoculum age of 24 h and 4% of inoculum volume. Response surface methodology (RSM) was used to evaluate the effect of three independent variables including pH, temperature and carbon source concentration on the Cr(VI) reduction. The presence of chromium in the microorganisms after the treatment was observed using SEM monograph and EDX spectra data. The maximum specific growth rate ( µ max ) of consortium was 0.1899 h −1 at the initial Cr(VI) of 5 mg/L.